Belief Adjustment Model Test in Investment Decision Making: Experimentation of short information Series - Aulida Kholifatun Nisa (STIE Perbanas Surabaya, 2017)
The aims of this study are examine the difference judgement given by investor using belief adjustment model to consider the pattern of presentation, the order of information and the tpye of information. This study using experimental design 2x2x2 mixed design, include: the pattern of presentation (Step by Step and End of Sequence), the order of information good news followed by bad news (++–) and bad news followed by good news (–++), and the type of information (accounting and non accounting). The hypothesis in this study were tested with Independence Sample T-test and Mann Whitney U. The participants were students STIE Perbanas Surabaya bachelor degree majoring in Accounting and Management who have knowlegde related to investment management and capital market or investment portfolio management and financial statements analysis. The result of this study showed that occurs recency effect while the pattern of information of Step by Step (SbS) and the type of information accounting and non accounting. This also occurs while the pattern of presentation of End of Sequence (EoS) and the type of acounting information occurs recency effect, wheares there was no order effect on the type of non accounting information.